Determinant Factors of Safety Impact to the School Buildings in West Sumatera - Indonesia. Issue 1 (1st May 2022) - Masril,; Mairizal,; Kurniawan, Deddy; Mohd Zin, Rosli; Ismail, Mohammad
Abstract: In visual observations focused on emergency service facilities in several building locations, it was found that several emergency service facilities were not available. In addition, the facility also does not meet the provisions so it is categorized in an unsafe condition. From these conditions, it is necessary to know the safety factor for the comfort and security of the building. This study aims to determine the safety factor and several other factors that affect safety in buildings. It is necessary to determine the critical factors that have a very high influence and, the strategies needed in planning, construction, and operations. This research uses qualitative and quantitative methods with SPSS and Smart PLS tools. A total of 20 questionnaires were given to respondents to get their opinion on the critical factors needed. The purpose of this research is to increase the knowledge base, especially in the field of developing school building safety standards in West Sumatra - Indonesia. The findings of this study are in the form of technical operation & maintenance factors that are influenced by systematic information systems and programs. In addition, safety factors are strongly influenced by building services, external environment, and operational & technical maintenance.